CITY PLACEMENT – INNOVATIONAL MEANS OF PROMOTING CITIES - Andrzej Szromnik (Polityki Europejskie, Finanse i Marketing)
A detail attempt of the “city placement” strategy, has been made in the article. Its main threads, components and decision making problems of the film producers teams have been emphasized. The author based his knowledge, in this case, on the diagnosis and analysis of the processes and decision making procedures adequate for big, Polish cities, their administrative authorities, promotional strategies and the rules of cooperation with media partners. Assumedly, the used process-structural conceptualization is to emphasize the main determinants of the “city placement” strategy introduction in marketing practice of the cities and regions.